2020
DOI: 10.1177/1475921720939616
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multilayer delaminations in composites using wavenumber analysis: numerical and experimental studies

Abstract: Delamination is one of the most common and dangerous failure modes for composites because it takes place and grows in the absence of any visible surface damage. The successful implementation of delamination detection in aerospace composite structures is always challenging due to the general anisotropic behavior of composites and multilayer delamination scenarios. This article presents a numerical and experimental investigation to detect and characterize the multilayer delaminations in carbon fiber–reinforced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The scattering directivity pattern has been shown to be influenced by the fibre orientation of the outer plies of the laminate, due to fibre steering effects [22]. Scattering patterns depend on the layup sequence, even for laminates with the same number of ply layers [34]. Mei et al found that the number of delaminations at the same location with different depths has an influence on the scattering pattern and the amplitude of trapped waves [35].…”
Section: Introductionmentioning
confidence: 99%
“…The scattering directivity pattern has been shown to be influenced by the fibre orientation of the outer plies of the laminate, due to fibre steering effects [22]. Scattering patterns depend on the layup sequence, even for laminates with the same number of ply layers [34]. Mei et al found that the number of delaminations at the same location with different depths has an influence on the scattering pattern and the amplitude of trapped waves [35].…”
Section: Introductionmentioning
confidence: 99%
“…21 However, defect identification using scattering studies typically requires understanding complex mode conversion phenomena, and basis conversion (wave-number/frequency) may be needed for estimating the strength of scattered signals. [22][23][24] On the other hand, wave visualization is a robust technique to identify the defects in any structure. Nevertheless, it consumes a large amount of data storage and acquisition time.…”
Section: Motivationmentioning
confidence: 99%
“…21 However, defect identification using scattering studies typically requires understanding complex mode conversion phenomena, and basis conversion (wave-number/frequency) may be needed for estimating the strength of scattered signals. 2224…”
Section: Motivationmentioning
confidence: 99%
“…However, this information is not known; therefore, it is important that during the design and development phase of any SHM system, a detailed investigation is carried out to choose the optimum parameters of the UGW (frequency, amplitude and mode), which will interact with probable damage types in the plate and enable a reliable damage detection. Many studies have been numerically carried out to capture the guided wave propagation properties in thin composite structures of different layups, materials, complexities and sizes numerically, since experimental investigations are often timely and expensive to allow a deeper understanding of the wave/damage interaction to optimise the parameters of the SHM system, towards condition-based maintenance concepts [ 5 , 11 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%